2016
DOI: 10.1124/mol.116.105080
|View full text |Cite
|
Sign up to set email alerts
|

α-Pinene, a Major Constituent of Pine Tree Oils, Enhances Non-Rapid Eye Movement Sleep in Mice through GABAA-benzodiazepine Receptors

Abstract: α-Pinene is a major monoterpene of the pine tree essential oils. It has been reported that α-pinene shows anxiolytic and hypnotic effects upon inhaled administration. However, hypnotic effect by oral supplementation and the molecular mechanism of α-pinene have not been determined yet. By combining in vivo sleep behavior, ex vivo electrophysiological recording from brain slices, and in silico molecular modeling, we demonstrate that (-)-α-pinene shows sleep enhancing property through a direct binding to GABA-ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 36 publications
4
87
0
3
Order By: Relevance
“…), has a specific binding site on aromatic residues of α1‐ and γ2‐subunits of GABA A ‐benzodiazepine receptors (Yang et al . ). Furthermore, the authors revealed that oral administration of α‐pinene enhanced the duration of nonrapid eye movement sleep, predominantly via the activation of GABA A receptors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), has a specific binding site on aromatic residues of α1‐ and γ2‐subunits of GABA A ‐benzodiazepine receptors (Yang et al . ). Furthermore, the authors revealed that oral administration of α‐pinene enhanced the duration of nonrapid eye movement sleep, predominantly via the activation of GABA A receptors.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, it has been reported that α‐pinene induces hypnotic activity via interaction with GABA A receptors (Yang et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, α-pinene was shown to induce cell cycle arrest and anti-tumor activity by controlling miR-221 [123], expending their functions on microRNA regulation. Moreover, 3-carene as well as α-pinene were shown to function as positive modulators for benzodiazepine (BZD)-receptors, exerting a sleep-enhancing effect upon oral administration [122,124], supporting the beneficial effects of forest bathing for patients with sleep disorders or anxiety.…”
Section: Functions Of Terpenes On Other Pathwaysmentioning
confidence: 99%
“…Alpha-pinene is considered a natural compound present not only in Cannabis sativa but also in essential oils of many aromatic plants, such as Lavender angustifolia, Rosmarinus officinalis, and coniferous trees [149]. Alpha-pinene is a bicyclo[3.1.1]hept-2-ene that contains a reactive 4-membered ring structure and exhibits antioxidant, antimicrobial, anti-tumor, hypnotic, and anxiolytic activities [83,120,[150][151][152]. There are different biological properties described to α-pinene, as well as essential oils containing this compound have been used to treat several diseases [153], although no affinity towards CBRs have been described [154].…”
Section: Alpha (α)-And β-Pinenementioning
confidence: 99%
“…Alpha-pinene has been extensively investigated in the last years for its medicinal properties that include sedative, hypnotic, and anxiolytic [152,155]. In this context, Yang and colleagues demonstrated that α-pinene interacts with GABA A /benzodiazepine receptors prolonging its synaptic transmission, significantly increasing the duration of non-rapid eye movement sleep (NREMS), and reducing sleep latency [151]. The beneficial effects of α-pinene are also extended to convulsions [80,81], ischemic stroke [82], and schizophrenia [156].…”
Section: Alpha (α)-And β-Pinenementioning
confidence: 99%